Putting the “Joy” in joint attention: affective-gestural synchrony by parents who point for their babies - Leavens, David A.; Sansone, Jo; Burfield, Anna; Lightfoot, Sian; O’Hara, Stefanie; Todd, Brenda K. (Frontiers in Psychology, 2014)
Despite a growing body of work examining the expression of infants' positive emotion in joint attention contexts, few studies have examined the moment-by-moment dynamics of emotional signaling by adults interacting with babies in these contexts. We invited 73 parents of infants (three fathers) to our laboratory, comprising parent-infant dyads with babies at 6 (n = 15), 9 (n = 15), 12 (n = 15), 15 (n = 14), and 18 (n = 14) months of age. Parents were asked to sit in a chair centered on the long axis of a room and to point to distant dolls (2.5 meters) when the dolls were animated, while holding their children in their laps. We found that parents displayed the highest levels of smiling at the same time that they pointed, thus demonstrating affective/referential synchrony in their infant-directed communication. There were no discernable differences in this pattern among parents with children of different ages. Thus, parents spontaneously encapsulated episodes of joint attention with positive emotion.